2017
DOI: 10.1039/c6cp08663b
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics, mechanisms and ionic liquids in the uptake of n-butylamine onto low molecular weight dicarboxylic acids

Abstract: Reactions of solid dicarboxylic acids with gaseous n-butylamine show an odd–even carbon dependence, with the odd carbon reactions forming ionic liquids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 119 publications
4
18
0
Order By: Relevance
“…The measured MA coating is thinner for this odd diacid vapor on the even SA diacid particle than coatings observed for MA on the odd diacid, GA. Alternating odd-even effects in the diacids have been observed in other systems, for example, in the uptake of amine vapors onto diacids,122,123 and in their physical properties such as melting points,123 sublimation temperatures,123 and vapor pressures 120. This may be related to the packing arrangement for even diacids, which has a more stable configuration than for the odd diacids.…”
Section: Resultsmentioning
confidence: 86%
“…The measured MA coating is thinner for this odd diacid vapor on the even SA diacid particle than coatings observed for MA on the odd diacid, GA. Alternating odd-even effects in the diacids have been observed in other systems, for example, in the uptake of amine vapors onto diacids,122,123 and in their physical properties such as melting points,123 sublimation temperatures,123 and vapor pressures 120. This may be related to the packing arrangement for even diacids, which has a more stable configuration than for the odd diacids.…”
Section: Resultsmentioning
confidence: 86%
“…Odd-carbon DCAs are more soluble, have higher vapor pressure, lower melting point and sublimation enthalpy. Recently, the odd/even alternation behavior on chemical reactivity was reported by Fairhurst and coworkers (Fairhurst et al, 2017) and, Zhao et al (2017) (Zhao et al, 2017) respectively, in the reactive uptake on solid C 3 -C 8 diacids films and chemical reactivity of submicron C 3 -C 7 dicarboxylic acid particles with gas-phase amines.…”
Section: Even-odd Alternation Of Diacids Reactivitymentioning
confidence: 82%
“…64 Besides inorganic acids, Fairhurst et al studied the reactions of amines with a series of solid diacids. 188,189 They found that butylaminium salts formed from evaporation of aqueous solutions of n-BA with C3, C5 and C7 diacids are viscous liquids, suggesting that ionic liquids form on the surface during the reactions of gas-phase amines with odd carbon diacids. 189 It is possible that ionic liquids may be formed via reactions of amines with the acidic components of semi-solid SOAs, which should be noticed.…”
Section: Other Reactions and Secondary Aerosolsmentioning
confidence: 99%